15.0k views
1 vote
2x³ + 3x² = x(x²) + (x- 2)² check weather the conditions is quadratic equation. plz help me guys. ​

User Katrine
by
4.8k points

1 Answer

2 votes

Answer:


2x\³ + 3x\² = x(x\²) + (x- 2)\² is not quadratic

Step-by-step explanation:

Given


2x\³ + 3x\² = x(x\²) + (x- 2)\²

Required

Determine if it is quadratic

We have:


2x\³ + 3x\² = x(x\²) + (x- 2)\²

Open brackets


2x\³ + 3x\² = x^3 + x^2 - 4x + 4

Collect like terms


2x\³ - x^3 + 3x\² -x^2 + 4x - 4=0


x^3 + 2x\²+ 4x - 4=0

A quadratic equation is represented as:


ax^2 +bx + c =0

Hence:


x^3 + 2x\²+ 4x - 4=0 is not quadratic

User Iliis
by
5.2k points